1993
DOI: 10.1093/nar/21.20.4824
|View full text |Cite
|
Sign up to set email alerts
|

In vivofootprinting of the human IL-2 gene reveals a nuclear factor bound to the transcription start site in T cells

Abstract: The IL-2 gene is a T cell specific gene that is expressed early during the activation-specific T lymphocyte development program. Electrophoretic mobility shift assay (EMSA) and DNase I footprinting assays have defined DNA/protein interactions at the IL-2 promoter cis-elements in vitro. To determine if the trans-activators documented in T cell nuclear extracts actually bind the IL-2 promoter in vivo, ligation mediated PCR (LMPCR) genomic footprinting was performed on the IL-2 promoter in both activated and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…The location of the in vitro-positioned nucleosome (Ϫ60 to Ϫ210) lies approximately within the bleomycin-footprinted region suggesting that the bleomycin footprint may in part represent a positioned nucleosome. It has previously been shown that a constitutive DNase I footprint occurs across the TATA box region of the IL-2 promoter in Jurkat T cells and this has been interpreted as representing a paused polymerase complex (40,41). Such a complex together with a FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The location of the in vitro-positioned nucleosome (Ϫ60 to Ϫ210) lies approximately within the bleomycin-footprinted region suggesting that the bleomycin footprint may in part represent a positioned nucleosome. It has previously been shown that a constitutive DNase I footprint occurs across the TATA box region of the IL-2 promoter in Jurkat T cells and this has been interpreted as representing a paused polymerase complex (40,41). Such a complex together with a FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments revealed that in resting mouse and human T cells, when the IL-2 gene is silent, the proximal promoter region is inaccessible to DNase I and restriction enzyme digestion. Following simulation, new DNase I hypersensitive sites appear suggesting changes in chromatin structure (37)(38)(39)(40)(41).…”
Section: T He Generation Of T Cell-mediated Immune Responses Ismentioning
confidence: 99%
See 1 more Smart Citation
“…The highly inducible nature of the IL-2 promoter seems to be the result of coordinate binding of many transcription factors to their recognition sequences on the promoter leading to the assembly of a functional unit (3,4,11,14,(21)(22)(23)(24). Such a unit has been termed an enhanceosome on the IFN-␤ promoter (25).…”
mentioning
confidence: 99%
“…It belongs to the Rel family of transcriptional regulatory proteins (26,31). The p50 subunit is specifically bound to an intron enhancer site in a number of eukaryotic genes (33)(34)(35)(36). NF-B is involved in cross-talk with other transcription regulators.…”
Section: Cholecystokinin (Cck)mentioning
confidence: 99%